A decision framework for green manufacturing indicators using fuzzy AHP - ELECTRE I: a case study of the steering system manufacturer. Issue 6 (2nd November 2021) - Sharma, Vikrant; Sharma, Vikram; Karwasra, Kritika
ABSTRACT: The manufacturing sector is now facing the challenge of complying with strict environmental regulations due to global warming, lack of natural resources, and waste management issues. Increased environmental problems and awareness lead to the implementation of green production practices by manufacturers worldwide. Green manufacturing (GM) activities form the basis of green and environmentally friendly goods production. There are, however, several possible indicators for GM implementation. There has been some good research on GM indicators, but little research in the Indian automotive industry has to date been undertaken on GM. In this analysis, the Fuzzy Analytical Hierarchy (F-AHP) method is incorporated into the Elimination Et Choix Traduisant La Realite (ELECTRE-I) procedure to define and rank the six main indicators as well as rank the case company's three plants for GM implementation. The proposed framework is accredited by a leading factory manufacturer of steering systems in India. This study shows that Efficiency of Environmental Management System and Hazardous Waste Management are the leading indicators for GM, and plant P1 is the best alternative for the six indicators among the three plants. Our research will support the priority setting of key indicators influencing green manufacturing practices in the automotive industry.